IRR-A Blunder-What Next? But it is Still Popular-Why? - Khata, Sitangshu (Indian Journal of Finance, 2008)
May be finance managers just enjoy living on the edge. What else would explain their weakness for using the internal rate of return (IRR) to assess capital projects? For decades, Finance textbooks and academics have warned that typical IRR calculations build in reinvestment assumptions that make bad projects look better and good ones look great. Yet, as recently as 2004, academic research found that three quarters of CFOs always or almost always use IRR when evaluating Capital projects (Anand,2002; Dedi & Orsag,2007 & Graham & Harvey, 2001).